Salvia chinensia Benth induces autophagy in esophageal cancer cells via AMPK/ULK1 signaling pathway - Jia, Lei; Lin, Xin-Rong; Guo, Wen-Yan; Huang, Ming; Zhao, Yang; Zhang, Yu-Shuang; Li, Jing (Frontiers in Pharmacology, 2022)
Salvia chinensia Benth. (Shijianchuan in Chinese, SJC) has been used as a traditional anti-cancer herb. SJC showed good anti-esophageal cancer efficacy based on our clinical application. However, the current research on SJC is minimal, and its anti-cancer effect lacks scientific certification. This study aims to clarify the inhibitory effect of SJC on esophageal cancer and explore its underlying mechanism. Q-Orbitrap high-resolution LC/MS was used to identify the primary chemical constituents in SJC. Cell proliferation and colony formation assays showed that SJC could effectively inhibit the growth of esophageal tumor cells in vitro. To clarify its mechanism of action, proteomic and bioinformatic analyses were carried out by combining tandem mass labeling and two-dimensional liquid chromatography-mass spectrometry (LC-MS). The results indicated that SJC could activate AMPK signaling pathway and effectively promote autophagy in esophageal cancer cells. Therefore, we further used WB to confirm that SJC activated autophagy in esophageal cancer cells through the AMPK / ULK1 signaling pathway. The results showed that P-AMPK and P-ULK1 were significantly up-regulated after the treatment with SJC. The ratio of autophagosomes marker proteins LC3II/I was significantly increased. In addition, the expression of the autophagy substrate protein P62 decreased with the degradation of autophagosomes. Using lentiviral transfection of fluorescent label SensGFP-StubRFP-LC3 protein and revalidation of LC3 expression before and after administration by laser confocal microscopy. Compared with the control group, the fluorescence expression of the SJC group was significantly enhanced, indicating that it promoted autophagy in esophageal cancer cells. Cell morphology and the formation of autophagosomes were observed by transmission electron microscopy. Our study shows that the tumor suppressor effect of SJC is related to promoting autophagy in esophageal tumor cells via the AMPK/ULK1 signaling pathway.